2012
DOI: 10.1093/nar/gks820
|View full text |Cite
|
Sign up to set email alerts
|

Promoters active in interphase are bookmarked during mitosis by ubiquitination

Abstract: We analyzed modification of chromatin by ubiquitination in human cells and whether this mark changes through the cell cycle. HeLa cells were synchronized at different stages and regions of the genome with ubiquitinated chromatin were identified by affinity purification coupled with next-generation sequencing. During interphase, ubiquitin marked the chromatin on the transcribed regions of ∼70% of highly active genes and deposition of this mark was sensitive to transcriptional inhibition. Promoters of nearly hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Both histones H2A and H2B are ubiquitinated in S and G 2 phases, deubiquitinated in prophase and then reubiquinated in anaphase 49 . Also, the promoter of certain active genes remains ubiquitinated during the entire mitosis to facilitate their transcriptional reactivation in post-mitosis 50 . Although the ubiquitin ligase RNF20 is associated to genome ubiquitination, potentially TRIP12 also participates in this epigenetic modification of histones during mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Both histones H2A and H2B are ubiquitinated in S and G 2 phases, deubiquitinated in prophase and then reubiquinated in anaphase 49 . Also, the promoter of certain active genes remains ubiquitinated during the entire mitosis to facilitate their transcriptional reactivation in post-mitosis 50 . Although the ubiquitin ligase RNF20 is associated to genome ubiquitination, potentially TRIP12 also participates in this epigenetic modification of histones during mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…This novel role of ubiquitin was first identified through a variant of ChIP-seq experiments that found ubiquitin present on certain sites during mitosis that were previously not described [108]. Those experiments showed that during interphase, ubiquitin was present on the chromatin of transcribed regions of transcriptionally active genes, consistent with the known function of PAF1C.…”
Section: Ubiquitin As a Mitotic Bookmarkmentioning
confidence: 65%
“…The fundamental difference between interphase and mitosis was a shift of the ubiquitin detected near promoters of the same genes that were previously ubiquitinated on their transcribed regions. For example [109], the GAPDH gene is heavily ubiquitinated over the gene body during G1 ( Figure 4A, indicated in blue), while during mitosis that ubiquitination over the gene body is absent but ubiquitination is detected over the promoter (Figure 4A, gold) [108]. The ubiquitinated promoter sites were consistently ubiquitinated at 150 bp upstream of the transcription start sites, suggesting a specific function relating each of these promoters.…”
Section: Ubiquitin As a Mitotic Bookmarkmentioning
confidence: 98%
“…Leukemia cells transformed by MLL-FP are more dependent on RNF20 to maintain their oncogenic transcriptional program than normal hematopoietic cells, which may relate to the altered transcriptional effector activity brought by the MLL-FP [55]. In addition to influencing HOX gene expression, RNF20 is required to mark genes in mitosis for sustained expression in interphase [56] and for genomic stability in other settings [57]. Overall, the PAFc and RNF20 appear to function to ensure high-level expression of genes critical for MLL-FP–initiated leukemogenesis.…”
Section: Constitutive Protein Interactorsmentioning
confidence: 99%